IDENTIFIKASI POTENTIALY INAPPROPRIATE MEDICATIONS PADA GERIATRI DENGAN PENYAKIT KRONIS DI UPTD PUSKESMAS X KABUPATEN KUNINGAN: IDENTIFICATION OF POTENTIALLY INAPPROPRIATE MEDICATIONS IN GERIATRIC WITH CHRONIC DISEASES AT UPTD PUSKESMAS X KUNINGAN - Salasanti, Citra Dewi; Iskandar, Rossa Deliana Putri; Alifiar, Ilham (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
The administration of medication and use of drugs in elderly patients must be carefully considered, as elderly patients are highly susceptible to adverse drug reactions. Beer’s and STOPP/START criteria are screening tools employed to prevent inappropriate drug use in geriatrics. This study aimed to determine the incidence of potentially inappropriate medications (PIMs) in geriatric with a history of chronic diseases at UPTD Puskesmas X. The research method was a cross-sectional observational study with prospective data collection from January to April 2024. The data was analyzed descriptively using the Beer’s 2023 criteria and STOPP/START version 3. The results of this study show that among the total sample, there were 185 geriatrics, with 132 (71.35%) females and 53 (28.65%) males. The most common chronic diseases observed were hypertension, diabetes mellitus, and osteoarthritis. According to the Beer’s criteria, there were 142 incidents of PIMs, while the STOPP criteria identified 16 incidents. Most of the drugs identified as PIMs based on both Beer’s and STOPP criteria were nonsteroid anti-inflammatory drugs (NSAIDs). Based on the results, PIMs occurred in geriatric who sought treatment from January to April 2024 at UPTD Puskesmas X. Therefore, it is necessary to enhance services and closely monitor therapy for geriatric. Keywords: Beer’s, Geriatric, STOPP START